2016
DOI: 10.4103/0973-1482.151935
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress marker in oral cancer: A review

Abstract: Oxygen derived species such as hydrogen peroxide, superoxide anion radical, hydroxyl radical (OH-), and singlet oxygen are well known to be cytotoxic and have been implicated in the etiology of a wide array of human diseases, including cancer. Various carcinogens may also partly exert their effect by generating reactive oxygen species (ROS) during their metabolism. Oxidative damage to cellular DNA can lead to mutations and may, therefore, play an important role in the initiation and progression of multistage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 5 publications
2
55
0
1
Order By: Relevance
“…NOS produces NO by catalyzing the conversion of L-arginine to L-citrulline, with concomitant oxidation of NADPH, which has slow down the velocity of the electrons in the respiratory chain to inhibiting the breath and reducing the consumption of oxygen, causing a state of stress leading to mitochondrial lipid peroxidation. [16] In our study, we observed NO levels were slightly enhanced in LBTI treatment (2314 ± 1.2 μM), as compared to VUTI (2290 ± 1.2 μM) and ASTI (2288 ± 1.2 μM) in HEK cells. However, significant increased levels of NO were observed in A549 cells treated with LBTI (3724 ± 1.2 μM), VUTI (3572 ± 1.2 μM), and ASTI (2968 ± 1.2 μM).…”
Section: Resultssupporting
confidence: 46%
“…NOS produces NO by catalyzing the conversion of L-arginine to L-citrulline, with concomitant oxidation of NADPH, which has slow down the velocity of the electrons in the respiratory chain to inhibiting the breath and reducing the consumption of oxygen, causing a state of stress leading to mitochondrial lipid peroxidation. [16] In our study, we observed NO levels were slightly enhanced in LBTI treatment (2314 ± 1.2 μM), as compared to VUTI (2290 ± 1.2 μM) and ASTI (2288 ± 1.2 μM) in HEK cells. However, significant increased levels of NO were observed in A549 cells treated with LBTI (3724 ± 1.2 μM), VUTI (3572 ± 1.2 μM), and ASTI (2968 ± 1.2 μM).…”
Section: Resultssupporting
confidence: 46%
“…By only including a few of the available studies, not referring to many scattered throughout the report and not mentioning ROS or oxidative stress in any conclusions or the executive summary, this important area of research was misrepresented. Oxidative stress is a toxic state which can lead to cellular DNA, RNA, protein or lipid damage (7,8), is accepted as a major cause of cancer (7), as well as being implicated in many reproductive, central nervous system, cardiovascular, immune and metabolic disorders (7)(8)(9)(10)(11)(12)(13)(14) further studies with improved methods. The evidence on effects on male subfertility is very limited, and allows no conclusions".…”
Section: Scientific Accuracymentioning
confidence: 99%
“…This altered micro-environmental activates the osteoclasts that initiate the resorption of alveolar bone. It is also believed that MMP-2 plays vital role in bone remodelling while MMP-14 (present at border of osteoclasts) helps for the interaction between matrix and osteoclasts [17,18]. The collagen remnants left over by osteoclasts in the lacunae of affected bones are cleared by MMp-13 already present in resorption lacunae [30].…”
Section: Biochemical Basis Of Periodontitismentioning
confidence: 99%